Nanotechnology assisted photo- and sonodynamic therapy for overcoming drug resistance - Rui Li; Zhimin Chen; Zhifei Dai; Yingjie Yu (Cancer Biology & Medicine, 2021)
Drug resistance is considered the most important reason for the clinical failure of cancer chemotherapy. Circumventing drug resistance and improving the efficacy of anticancer agents remains a major challenge. Over the past several decades, photodynamic therapy (PDT) and sonodynamic therapy (SDT) have attracted substantial attention for their efficacy in cancer treatment, and have been combined with chemotherapy to overcome drug resistance. However, simultaneously delivering sensitizers and chemotherapy drugs to same tumor cell remains challenging, thus greatly limiting this combinational therapy. The rapid development of nanotechnology provides a new approach to solve this problem. Nano-based drug delivery systems can not only improve the targeted delivery of agents but also co-deliver multiple drug components in single nanoparticles to achieve optimal synergistic effects. In this review, we briefly summarize the mechanisms of drug resistance, discuss the advantages and disadvantages of PDT and SDT in reversing drug resistance, and describe state-of-the-art research using nano-mediated PDT and SDT to solve these refractory problems. This review also highlights the clinical translational potential for this combinational therapy.